Pembuatan Pektin Dari Wortel dan Pemanfaatannya dalam Formulasi Pasta Gigi - Al'farisi, Cory Dian; Mutamima, Anisa; Drastinawati, Drastinawati; Yelmida, Yelmida; Siahaan, Daniel Andica; Az Zahra, Alya (Stannum : Jurnal Sains dan Terapan Kimia, 2025)
Pectin, a complex polysaccharide derivative, is abundantly found in various fruits and vegetables. Due to its gel-forming ability, pectin plays a crucial role in the production of diverse food products, including jam, jelly, fruit preparations for yogurt, fruit juice, and others. The primary aim of this research was to ascertain the yield and extract the pectin content from carrots and investigate the impact of incorporating different concentrations of pectin into toothpaste formulations, comparing them against the SNI 12-3524-1995 standard. In this study, concentrations of pectin in toothpaste formulations were varied at 2.5%, 3%, 3.5%, and 4%. Pectin characteristics, encompassing yield, moisture content, equivalent weight, and methoxyl content, were examined, alongside assessments of toothpaste formulation characteristics, including organoleptic evaluation, pH testing, and spreadability testing. The research findings revealed that 13 grams of dried carrot powder yielded 1.17 grams of pectin, resulting in a 9% yield, 6.7% moisture content, an equivalent weight of 717 g/gmol, and a methoxyl content of 9.3%. Toothpaste testing indicated pH values of 7.63, 7.7, 7.26, and 7.06 for concentrations of 2.5%, 3%, 3.5%, and 4%, respectively. Organoleptic evaluations for each concentration revealed a thick texture, light brown and brown color, and mint and mild mint aromas. Spreadability test results for concentrations of 2.5%, 3%, 3.5%, and 4% were 3.1 cm, 3 cm, 2.8 cm, and 2.8 cm, respectively. While increasing the concentration of carrot pectin did not significantly impact the pH, color, aroma, and texture of the toothpaste formulation, it led to a decrease in spreadability.